The Internalization of Moral Values in Wayang Kulit: The Tale of Begawan Among Raga (An Ethnopedagogical Perspective) - Anis Mirna Defi (Global Action and Education for Society, 2025)
Efforts to strengthen identity related to the existence of wayang kulit (shadow puppetry) are being intensively carried out by the community, particularly artists. Ki Dalang Roman and the wayang kulit troupe of the gagrak trowulanan style have engaged in cultural innovations to preserve the art of wayang kulit. The Lakon Carangan (non-canonical stories) serves as a solution to address the challenges posed by global cultural influences. This study focuses on the meaning of character reinforcement within society through Ki Dalang Roman’s wayang kulit gagrak trowulanan performance of Lakon Begawan Among Raga and explores the process of internalizing moral values from this wayang kulit tale in educational settings. The tale, which has been performed in various shows, carries diverse meanings that are instrumental in strengthening societal character. It is not merely a narrative but is intended as an educational tool. Every Lakon Carangan or story presented always incorporates moral values, which are expected to shape society's character positively and achieve harmony.